Chromosomal mutagenesis in human somatic cells: 30-year cytogenetic monitoring after chornobyl accident - Pilinska, M.A.; Shemetun, G.M.; Shemetun, O.V.; Dybsky, S.S.; Dybska, O.B.; Talan, O.O.; Pedan, L.R.; Kurinnyi, D.A. (Experimental Oncology, 2016)
In the lecture we have generalized and analyzed the data of cytogenetic laboratory of National Research Center for Radiation Medicine of the National Academy of Medical Sciences of Ukraine on 30-year selective cytogenetic monitoring among the priority contingents of different ages exposed to radiation after Chornobyl accident in Ukraine. It is highlighted that not only targeted but also untargeted radiation-induced cytogenetic effects should be explored, especially in delayed terms following radiation exposure. The new methodical approaches for studying “bystander effect”, individual radiosensitivity, and various forms of radiation-induced chromosomal instability (delayed, hidden, transmissible) have been proposed. These approaches proved to be advantageous for analyzing cytogenetic patterns of induction and persistence of chromosomal instability in human somatic cells because of “bystander effect” and “bystander type effect”. The phenomenon of positive “reverse” bystander effect has been found. The possibility of modifying the inherited individual human susceptibility to mutagenic exposure by ionizing radiation has been estimated. Finally, the association between hypersensitivity to radiation exposure and realization of oncopathology in exposed individuals has been revealed. The increased intensity of human somatic chromosomal mutagenesis was confirmed not only in the nearest but in the delayed terms following Chornobyl accident as a result of radiation-induced both targeted and untargeted cytogenetic effects. Such effects can be considered as risk factors for malignant transformation of cells, hereditary diseases, birth defects, and multifactorial somatic pathology. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.